1970
DOI: 10.1172/jci106246
|View full text |Cite
|
Sign up to set email alerts
|

The integrity of the ether linkage during thyroxine metabolism in man

Abstract: A B S T R A C T The structures of thyroxine metabolites after total deiodination bear on the mode of thyroxine (Ti) action in vivo. The present study was undertaken to determine the integrity of the ether linkage during thyroxine metabolism in man. Normal volunteers were given simultaneous intravenous injections of two thyroxines labeled with either "C or 'H on the opposite sides of the ether linkage, D,L-[a,f-'H]Ti and D,L-[phenolic ring-"C] T4. The ratio of alanine side chain to phenolic ring which was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1971
1971
1985
1985

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Hence, according to this formulation, inhibition of catalase would favor DIT formation by permitting the accumulation of H202, thereby promoting peroxidase-mediated cleavage of the ether bond of T4. Conversely (21)(22)(23) showed that after the administration of T4 variously labeled with either 14C or 3H in its outer ring, inner ring, or alanine side chain, a major fraction of administered radioactivity was recovered in urinary metabolites containing radionuclides from the three portions of the T4 molecule. Although these studies clearly suggested that the major pathways of T4 metabolism do not involve the cleavage of the ether bond, they were not strictly quantitative and could not rigorously exclude, therefore, the possibility that some portion of T4 was metabolized by cleavage of the ether link to yield DIT.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, according to this formulation, inhibition of catalase would favor DIT formation by permitting the accumulation of H202, thereby promoting peroxidase-mediated cleavage of the ether bond of T4. Conversely (21)(22)(23) showed that after the administration of T4 variously labeled with either 14C or 3H in its outer ring, inner ring, or alanine side chain, a major fraction of administered radioactivity was recovered in urinary metabolites containing radionuclides from the three portions of the T4 molecule. Although these studies clearly suggested that the major pathways of T4 metabolism do not involve the cleavage of the ether bond, they were not strictly quantitative and could not rigorously exclude, therefore, the possibility that some portion of T4 was metabolized by cleavage of the ether link to yield DIT.…”
Section: Discussionmentioning
confidence: 99%
“…Since the clearance rate of Tetrac was reported to be slower than that of T3 by some early studies, the higher serum concentrations of "4C-labeled Tetrac could not be interpreted to mean a higher production rate for Tetrac than for T3 in man (25). Recently, Pittman, Read, Chambers, and Nakafuji (13) ratios of the urine were the same as the 3H/'4C ratios of the T4 dose suggesting that the deiodinated metabolites of T4 retained an intact diphenyl ether structure. Therefore, most likely the T3 and Tetrac formed from T4 metabolism are in turn deiodinated before urinary excretion without undergoing cleavage of the diphenyl ether.…”
Section: Discussionmentioning
confidence: 99%
“…The purity of radioactive T4 and T3 was 98% or greater before use. They were prepared for injection in a sterile solution of 1% ethanol, 0.9% scdium chloride, and 1% human albumin as described previously (13). Every thyroxine dose was chromatographed in at least two solvent systems and the presence of triiodothyronine was assayed directly in a liquid scintillation counter as de- Subjects.…”
Section: Methodsmentioning
confidence: 99%